(untitled) (Research, Society and Development, 2020)
Talking about humanization is fundamental; listening to the patient is essential. Through the patient’s perception of the care being provided, quality of care can be assessed, thus contributing to the well-being of those institutionalized. The objective of this work is to know and analyze the satisfaction of hospitalized patients in relation to the care of the multidisciplinary team, verifying the needs found during the hospitalization period. This is an Integrative Review study, with a narrative approach. To answer the study question, a search was carried out in the VHL-Bireme, MedLine, Lilacs, BDENF-Enfermagem, Scielo databases, using the terms: “Patient care team” “Empathy” “Humanization in care” The results of this research underscore effective communication as a key point for the smooth running of teamwork, also highlighting the satisfaction that the patient has in relation to the professional who serves him with a holistic view and the importance of evaluating the care provided, thus being able to provide improvement in the practices developed, qualifying the assistance even more.